Trying to become somebody else: Somos ainda induzidos pelos retratos das vedetas de cinema? - Duarte, Joana Isabel (Revelar: Revista de Estudos da Fotografia e Imagem, 2019)
The photographs of movie stars - particularly the publicity portraits created by still photographers, in order to promote the star and lor the films in which he/she participates - constituted, between the decades of 20 to so of the 2oth century, a fundamental part of the complex network of the star system, impelling a growing cult to the stars and triggering processes of identification and emulation regarding those portrayed. The presence of the portraits of movie stars in the visual culture of the 2oth century is undeniable: it has been conveyed through magazine covers, books, posters, printed cards. The photography of stars calls for reflection themes such as the reception of these images in the viewers and portrait as an "object of cult" and ersatz of the person portrayed; to the point that some photos of the stars prove to be much more iconic (because they are actually seen and known) than the films themselves. The present article intends to reflect on the portraits of stars, the role and contribution of this photographic genre in the formation of an admiration, "idolatry" and mimicry of the vedette. This study will be based on the analysis of primary sources such as periodical specialized press, studies of the history of photography, cinema and anthropology. Understanding how we are induced by these portraits and reflecting in the present on the permanence of its original role - that of enchanting us and making us dream - is, therefore, one of the aims of this work.